Proposed new interior design scheme of Warisan Seni Keris Gallery for Perbadanan Kemajuan Kraftangan Negeri Perak at PT 4107 & 4108 Persiaran Sultan Yusof Izuddin Shah, Lumut, Perak / Noor Fadhilah Mohd Nor - Mohd Nor, Noor Fadhilah (Faculty of Architecture, Planning and Surveying, 2012)
This Diploma level of Interior Design final project is towards student understanding about the interior design project’s in the whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project for my final semester is as proposed new interior design of Warisan Seni Keris Gallery for Perbadanan Kemajuan Kraftangan Cawangan Perak at PT407 Persiaran Sultan Yusuf Izuddin Shah, Lumut, Perak. The gallery authority itself has play a big role in providing and promoting traditional malay weapon towards local citizen and foreigner. Thus, it was an honor for me to get involved with the authority in making their gallery as a part of my final years project. The concept and image is also apply to both interior and exterior to appeal the centre will be able to lure more tourists and visitors who were always keen in our aesthetic value in architecture. There were several researches dine to succeed this tourist information centre final project, amongst them are site analysis, building analysis, interview, observation and case studis. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Warisan Seni Keris Gallery demands in term of function and aesthetic value.